Effect of initial knee angle on the squat-jump performance - Ng, Yee Shuang (2022)
The study aimed to investigate the effect of initial knee flexion angle on squat-jump performance. Since squat depth can influence squat-jump performance, it is important to find out how deep should a person squat to achieve the optimal squat-jump performance. This allows sustainable training programs for various sports activities to be defined and allows players to maximize their performance. Fifteen female subjects (24 ± 2 years, 163 ± 3 cm, and 54 ± 5 kg) warmed up with 3 sets of 8 repetitions of squat-jump at the preferred depth, followed by the manipulation squat-jump at different squat depths of 30.0 cm, 37.5 cm, 45.0 cm, 52.5 cm, and 60.0 cm, which corresponded to the knee flexion angle of 60º, 75º, 90º, 105º, and 120º. The flight time, peak speed, peak propulsive force, maximum concentric power, and flight height of each squat-jump were recorded by the BTS G-Walk® sensor and were statistically analyzed. Increasing knee flexion angle corresponded to an increase in propulsive peak force but a decrease in flight time, peak speed, and flight height while the maximum concentric power slightly increased up to 75º followed by a drastic decrease. The quadratic regression analysis has shown that the initial knee flexion angle was significantly correlated to all biomechanical parameters (p < 0.05). Flight height (r = 0.732, r 2 = 0.536) and flight time (r = 0.715, r 2 = 0.511) had better fit to the regression model of knee flexion angle than other biomechanical parameters (r < 0.7, r 2 < 0.5). Besides, flight height had strong positive linear correlations with flight time (r = 0.985, r 2 = 0.854, p < 0.05) and peak speed (r = 0.921, r 2 = 0.849, p < 0.005.Maximal flight time, peak speed, and flight height, as well as minimal propulsive peak force, were produced at 60º whereas maximal maximum concentric power was produced at 75º. The best squat-jump performance was observed at 60º, which was the smallest knee flexion angle in this study.